EREJA YANG MELAYANI MENURUT EVANGELII GAUDIUM DI ZAMAN REVOLUSI INDUSTRI 5.0 - Maria Nesta Sabambam; Theresia Aryanti Mando Tato; Julianti Fingky; Marsela Sadaria Duha; Helena Hay Leu (Jurnal Pelayanan Pastoral, 2024)
The Church is a community of believers called to serve one another and help those around them in various forms of service, such as charitable activities, social assistance, and emotional support. In carrying out these missionary tasks, the Church often faces challenges, both from outside and from within itself and it is inevitable that in many such situations the Church continues to expand the scope of its ministry. The Church is called in the era of the industrial revolution 5.0. The Industrial 5.0 era typically includes developments such as connected manufacturing, high levels of automation, and more profound use of technology in industrial processes. The role of the Church or religion in this context may vary depending on how society and the Church itself respond to technological change and social dynamics. Some possible considerations regarding the role of the Church in the Industry 5.0 era include: Ethical considerations related to technology: The Church can engage in educating its congregation on the ethical use of technology, including artificial intelligence, automation, and high connectivity. This may involve articulating an ethical perspective on the use of technology to ensure that these developments benefit the common good and protect human dignity. In the context of Industry 5.0, society is likely to be increasingly digitally connected. Churches may wish to consider ways to form and nurture online communities to support spiritual growth and friendship. However, it is important to note that church responses to these changing times may vary and not all churches adopt modern technology in the same way. This depends on the specific values and traditions of each ecclesial community.